Qualitative colorimetric analysis of a Ir(iii)/Eu(iii) dyad in the presence of chemical warfare agents and simulants on a paper matrix. Issue 14 (6th March 2019) - Dennison, Genevieve H.; Curty, Christophe; Metherell, Alexander J.; Micich, Eva; Zaugg, Andreas; Ward, Michael D.
Abstract : A dual emissive Ir(iii )/Eu(iii ) dyad in a paper-based luminescence assay for liquid chemical warfare agents demonstrated clear visual responses. Abstract : The addition of G- and V-series organophosphorus chemical warfare agents and simulants to a paper-based assay of a dual-luminescent Ir(iii )/Eu(iii ) dyad generated different emissive responses between the classes and compound types. The emission responses are complex and based not only on altering the balance between red Eu(iii )-based and blue Ir(iii )-based luminescent components, but also incorporate other factors such as analyte volatility, concentration and UV absorption. The extent of this emission colour change was analysed colorimetrically and related to the change in RGB output over time.